REPLACEMENT AND BOOK VALUE. - Ashley, C. A. (The Accounting Review, 1944)
Abstract The article discusses the advisability of discarding a fixed asset which can still be used and which may still be capable of earning profits and substituting for it a newer model. The author further states the fact that depreciation and obsolescence are sometimes treated as separate problems. If it is no longer wise to use an asset because new methods produce greater profits, then that asset has only a scrap value, it may have depreciated in use or it may have been used hardly at all, but it is obsolete, and must be written off. An asset is obsolete if the prime costs of using it are greater than the total costs of equivalent production using a new asset in its place. Businessmen may hesitate before scrapping an asset because it has become obsolete in the sense in which the word is defined above. Conditions may change and, unless the margin of benefit is considerable, it will be advisable to wait until the benefit appears to be permanent. In competitive industries, a failure to scrap old equipment may lead to heavy loss because a lower selling price will soon be fixed, based on the costs of production by the new method.